Pengaruh Kegiatan Senam Fantasi Terhadap Kecerdasan Kinestetik Anak Kelompok B Di Tk Pertiwi 01 Girilayu Matesih Karanganyar Tahun Ajaran 2016/2017 - Pujiastuti, Nurul, Drs. Haryono Yuwono,SE,. M. Pd (2017)
The problem of this research was that the development and the stimulation kinestethic intelligence of children are not optimal yet. It was proven that when gymnastics activities done were not vary, the children were not interested and borred. Conseqvently the gymnastic was not done. The purpose of this research was to determine the influence of gymnastics fantasy activities toward children intelligence in group B at TK Pertiwi 01 Girilayu Matesih Karanganyar in the Academic Year of 2016/2017. This research used Pre-Eksperimental Designs by one group pretest-postest. The data collection technique from this research used observation, interview, documentations and test. The data analysis compairied, the magnitude of "t" that collected after the calculation (t0 = 23,30). It could be known t0 bigger than tt, that was: tt 2,09< t0 23,30 > tt 2,86. Because t0 bigger than tt, that the naught hypothesis submitted was rejected. The result of this experiment convicely can said that the gymnastic fantasy can be influence the children's kinesthetic intelligence in group B at TK Pertiwi 01 Girilayu Matesih Karanganyar. Keywords : Gymnastics Fantasy, Kinesthetic Intelligence